Влияние Индустрии 4.0 на развитие высшего бухгалтерского образования в России - I. V. Kalnitskaya; O. V. Maksimochkina (Учёт. Анализ. Аудит, 2024)
The purpose of the research is to analyze the impact of Industry 4.0 technologies on the development of higher accounting education in Russia through the transformation of the accounting profession. Opinions about the future of the latter differ, which negatively affects the demand for higher accounting education and thereby limits the opportunities of the younger generation to build a career in the financial sector of the economy. Regarding the debate on this issue, the authors are convinced in the operation of Amara’s Law: the destructive power of Industry 4.0 for the accounting profession is overestimated in the short run while its innovative component is underestimated in the long run. The authors see opportunities for restoring the high status of accounting education in the country in positioning a new vision of the profession; a return to the classical Russian system of higher education; transition from an academic teaching method to a practice-oriented one; change of the educational trajectory (from education “for life” to “lifelong” education). While conducting the research such methods like integrated and systematic approaches, analysis and synthesis were used. The results of the research should draw the attention of stakeholders to methods and programs of training highly qualified specialists in the field of accounting, analysis and audit for the domestic digital economy.